Serum Bilirubin after Acute Ischemic Stroke is Associated with Stroke Severity - Luo, Yun; Li, Jing-Wei; Lu, Zheng-Juan; Wang, Chong; Guan, De-Ning; Xu, Yun (Current Neurovascular Research, 2012)
Elevated serum bilirubin was prevalent in the acute ischemic stroke (AIS), which was induced in response to oxidative stress and could display the intensity of oxidative stress. As more severe stroke is linked with higher level of oxidative stress, we hypothesized that bilirubin may be associated with the severity of stroke. In this study, bilirubin and other biochemical indexes were measured in 531 enrolled patients with AIS, and NIH Stroke Scale (NIHSS) scores were assessed simultaneous with blood collection. The association between bilirubin and the severity of stroke was performed by Spearman correlation analyze, and the level-risk relationship of bilirubin in different level of NIHSS score was performed through Multinomial logistic regression analysis. We performed multivariable logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI) of severe stroke dichotomized as NIHSS≥8 with adjustment for other stroke risk factors, the level-risk relationship of severe stroke in different level of bilirubin was also performed through Multinomial logistic regression analysis. We found that NIHSS score was significantly positively correlated with both serum direct bilirubin (Dbil, R=0.229 and P=0.000) and total bilirubin (Tbil, R=0.224 and P=0.000), higher level of serum bilirubin linked to the higher NIHSS score with OR(95% CI) in upper level of NIHSS score group was 1.12(1.01-1.24), 1.23(1.11-1.36), 1.31(1.15-1.51) in Dbil and 1.01(0.99-1.31), 1.05(1.03-1.08), 1.07(1.03-1.11) in Tbil compared to the lowest level group. In unadjusted or adjusted logistic regression analyses, serum Dbil and Tbil still have a significant association with the severe stroke. When both the Dbil and Tbil concentrations were grouped into 4 levels, participants with higher levels of bilirubin showed higher risk with severe stroke compared with the lowest level of bilirubin, with OR(95% CI) 1.881(1.04-3.404) of Dbil in level 3 and 3.702(1.979-6.927) of Tbil, 3.352(1.572-7.147) of total bilirubin in level 4. As a conclusion, serum bilirubins were in significant correlation with severity of AIS, which may be served as useful markers to reflect the degree of illness.
Keywords: Bilirubin